Opportunities for ethnographic methodologies in B2B service research - Keränen, Joona; Prior, Daniel D. (Emerald, 2019)
Purpose This paper highlights the suitability, application and fruitful opportunities for ethnographic methodologies in contemporary B2B service research. Design/methodology/approach This paper is based on a literature review and conceptual analysis of ethnographic research methodology and B2B service literatures. Findings This paper discusses the central features of ethnographic research methodologies, their key differences to other qualitative methodologies, key trends in contemporary B2B service research and opportunities for ethnographic research methodologies in selected priority areas. Research limitations/implications: This paper highlights the opportunities, unique strengths and specific advantages of ethnographic research methodologies to advance B2B service research and theory development. Practical implications: This paper encourages B2B firms to undertake ethnographic field projects to better understand customers’ roles, experiences and usage processes that relate to B2B services. Originality/value: Ethnographic research approaches have been largely overlooked or neglected in B2B service research. This paper highlights their potential, suggests areas for application and encourages B2B service researchers to adopt ethnographic approaches to delve deeper into the social and cultural aspects of B2B services
Keywords: Qualitative research; Ethnography; business-to-business services; customer engagement; customer experience; participant observation; lived experiences